KANK2 Links αVβ5 Focal Adhesions to Microtubules and Regulates Sensitivity to Microtubule Poisons and Cell Migration - Paradžik, Mladen; Humphries, Jonathan D.; Stojanović, Nikolina; Nestić, Davor; Majhen, Dragomira; Dekanić, Ana; Samaržija, Ivana; Sedda, Delphine; Weber, Igor; Humphries, Martin J.; Ambriović-Ristov, Andreja (Frontiers in Cell and Developmental Biology, 2020)
Integrins are heterodimeric glycoproteins that bind cells to extracellular matrix. Upon integrin clustering, multimolecular integrin adhesion complexes (IACs) are formed, creating links to the cell cytoskeleton. We have previously observed decreased cell migration and increased sensitivity to microtubule (MT) poisons, paclitaxel and vincristine, in the melanoma cell line MDA-MB-435S upon transfection with integrin αV-specific siRNA, suggesting a link between adhesion and drug sensitivity. To elucidate the underlying mechanism, we determined αV-dependent changes in IAC composition. Using mass spectrometry (MS)-based proteomics, we analyzed the components of isolated IACs of MDA-MB-435S cells and two MDA-MB-435S-derived integrin αV-specific shRNA-expressing cell clones with decreased expression of integrin αV. MS analysis showed that cells preferentially use integrin αVβ5 for the formation of IACs. The differential analysis between MDA-MB-435S cells and clones with decreased expression of integrin αV identified key components of integrin αVβ5 adhesion complexes as talins 1 and 2, α-actinins 1 and 4, filamins A and B, plectin and vinculin. The data also revealed decreased levels of several components of the cortical microtubule stabilization complex, which recruits MTs to adhesion sites (notably liprins α and β, ELKS, LL5β, MACF1, KANK1, and KANK2), following αV knockdown. KANK2 knockdown in MDA-MB-435S cells mimicked the effect of integrin αV knockdown and resulted in increased sensitivity to MT poisons and decreased migration. Taken together, we conclude that KANK2 is a key molecule linking integrin αVβ5 IACs to MTs, and enabling the actin-MT crosstalk that is important for both sensitivity to MT poisons and cell migration.